Research Trends in Science Literacy in Education: A Bibliometric Analysis for the Period 2022-2025 - Diky Nurkhoerudin; Daru Wahyuningsih; Anis Nazihah; Anif Jamaluddin (Unnes Science Education Journal, 2026)
Scientific literacy has become a key competency in contemporary science education, particularly amid the post-pandemic landscape marked by accelerating digitalization, expanding access to information, and growing demand for evidence-based decision-making. Although literature on scientific literacy continues to expand, understanding of recent research developments remains limited. This study aims to examine research trends, intellectual structures, and emerging themes in scientific literacy research within educational contexts from 2022-2025. A bibliometric approach was adopted using data retrieved from the Scopus database through a systematic search and screening process guided by the PRISMA framework, with publications analyzed via Microsoft Excel and VOSviewer to assess publication growth, geographical and institutional contributions, citation performance, and keyword co-occurrence networks. The results indicate a substantial increase in publication output after 2023, with the United States, Indonesia, and China as leading contributors, reflecting the global scope of the field and disparities in national research capacities. Institutional analysis reveals broad participation across universities and research organizations, while citation and keyword analyses point to inquiry-based learning, scientific reasoning, critical thinking, and emerging themes including socioscientific issues and technology-enhanced education. These findings signal a shift toward competency-based frameworks emphasizing reasoning and evidence evaluation, informing curriculum development and future research.